Advancing perspectives on health literacy in childhood and youth. (29th May 2019) - Bröder, Janine; Okan, Orkan; Bauer, Ullrich; Schlupp, Sandra; Pinheiro, Paulo
Abstract: Children and young people's importance as core target population for health literacy has been highlighted throughout the literature due to the relevance of the early life phases for maintaining, restoring and promoting health during the life course. Transferring health literacy concepts to the target population, however, requires proper testing of their applicability and their fit to the developmental phases as well as the target populations' realities and needs. This article aims to discuss children's and young people's health literacy by elaborating and exploring childhood and youth as life phases with unique characteristics from multidisciplinary perspectives. Drawing on theories and findings from developmental studies, sociology and socialization research, health literacy in childhood and youth is discussed along five 'D' dimensions: (i) disease patterns and health perspectives, (ii) demographic patterns, (iii) developmental change, (iv) dependency and (v) democracy. The unique particularities of children and young people relevant for health literacy include their disease and health-risk profiles, their vulnerability to demographic factors, their social role and status, and their right to participation. Inter- and intra-generational relationships and an unequal distribution of power can either promote or hinder children and young people's health literacy development and their opportunities for participating in health-related decision making. Specifying what is called the 'contextual' and 'relational' dimension of health literacy for the target group requires considering their personal attributes and agency as contextually embedded and interrelated. Taking these considerations into account can help to move towards a more tailored and holistic approach to health literacy of children and young people.